2007
DOI: 10.1002/app.26162
|View full text |Cite
|
Sign up to set email alerts
|

Application of polypyrrole to flexible substrates

Abstract: Conducting polymers such as polypyrrole may be useful in smart packaging products, provided application methods can be developed that circumvent the insolubility and infusibility of these materials. Experiments were conducted in five research areas relevant to the application of polypyrrole to nonrigid substrates. The studies reveal that application of polypyrrole from the liquid phase, either by deposition from depleted bulk solution or inkjet printing dispersions, is unlikely to give films as regular as thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…To enable the manufacturing of conducting polymer layers on cellulose with varying thickness, layer-by-layer techniques have been proposed based on deposition from solutions containing oligomers [17,35], vapor polymerization [34,36] and deposition from polymer solutions in organic solvents [37]. However, to the best of our knowledge, the influence of the cellulose substrate on the electrochemical performance of the composites has not yet been systematically studied.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To enable the manufacturing of conducting polymer layers on cellulose with varying thickness, layer-by-layer techniques have been proposed based on deposition from solutions containing oligomers [17,35], vapor polymerization [34,36] and deposition from polymer solutions in organic solvents [37]. However, to the best of our knowledge, the influence of the cellulose substrate on the electrochemical performance of the composites has not yet been systematically studied.…”
Section: Introductionmentioning
confidence: 98%
“…In situ polymerization of conducting polymers on cellulose can be carried out based on three main approaches involving (i) mixing or soaking the cellulose in a monomer solution followed by addition of the oxidant [18], (ii) soaking the cellulose in a solution of the oxidant followed by addition of monomer solution [33] and (iii) soaking of the cellulose in oxidant solution followed by addition of monomer from the vapor phase [34]. To enable the manufacturing of conducting polymer layers on cellulose with varying thickness, layer-by-layer techniques have been proposed based on deposition from solutions containing oligomers [17,35], vapor polymerization [34,36] and deposition from polymer solutions in organic solvents [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, for many packaging applications where cost rather than quality is the principal driver, inkjet resolutions may be adequate. From the SEMs, it was clear that the PPydye was absorbed into the paper substrate with no evidence of a separate surface layer, whereas on PEDOT-coated PET, the PPy-dye layer had a porous appearance typical of PPy films applied by VPP [7]. Measurements on SEM cross-sections indicated that the PPy layer was 1.4-1.5 lm thick, while the PEDOT layer was thinner, at 0.4-0.5 lm.…”
Section: Application Of Oxidant-dyementioning
confidence: 91%
“…The key advantage of chemical polymerisation is that it potentially allows the use of high-volume, reel-to-reel printing processes that reduce unit costs in industrial-scale production [6,7]. The greater simplicity of printing methods compared with electrochemical polymerisation could widen the range of economically feasible applications of dye release technology, perhaps even to the extent of allowing use in packaging products, which are notoriously cost-sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…10 illustrate that the deposition on non-absorbent surface (glass) led to conductivities quite an order of magnitude higher than those obtained on absorbent surface (copy paper). Indeed, the substrate topography and its chemical nature affect the coating drying mechanism and consequently its conductivity (Winther-Jensen et al 2007;Denneulin et al 2008). Smooth, nonabsorbent substrates led to the formation of homogeneous PPy/NFC films (Fig.…”
Section: Conductivity As a Function Of Temperaturementioning
confidence: 98%